1998
DOI: 10.1021/ac971063b
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic Sorting of Particles and Cells in a Microsystem

Abstract: There are highly sensitive analytical techniques for probing cellular and molecular events in very small volumes. The development of microtools for effective sample handling and separation in such volumes remains a challenge. Most devices developed so far use electrophoretic and chromatographic separation methods. We show that forces generated by ac fields under conditions of negative dielectrophoresis (DEP) can also be used. Miniaturized electrode arrays are housed in a microchannel and driven with high-frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
304
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 403 publications
(312 citation statements)
references
References 29 publications
1
304
0
3
Order By: Relevance
“…Unfortunately, the same situation in medical diagnosis of pathogenic bacteria is observed because traditional colony counts methods are always slow (up to 72 h). Obviously, there are some new technologies such as: PCR detection [2], flow cytometry [3,4], differential staining [5], serological methods and recently dielectrophoresis [6][7][8][9][10][11][12][13][14][15][16][17], or microchipbased technology [18]. For instance, PCR method is extremely sensitive, however requires pure samples and hours of analysis and expertise in molecular biology.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the same situation in medical diagnosis of pathogenic bacteria is observed because traditional colony counts methods are always slow (up to 72 h). Obviously, there are some new technologies such as: PCR detection [2], flow cytometry [3,4], differential staining [5], serological methods and recently dielectrophoresis [6][7][8][9][10][11][12][13][14][15][16][17], or microchipbased technology [18]. For instance, PCR method is extremely sensitive, however requires pure samples and hours of analysis and expertise in molecular biology.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that particles can be focused in three dimensions using electric field cages, and also in twodimensions within a fluid stream [11][12][13]. A small channel, typically 50 mm across is microfabricated with pairs of electrodes on the top and bottom.…”
Section: Introductionmentioning
confidence: 99%
“…A small channel, typically 50 mm across is microfabricated with pairs of electrodes on the top and bottom. Using negative dielectrophoresis, particles are repelled from the electrode edges and form a tight beam in the channel centre [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations